2015
DOI: 10.1109/tgrs.2015.2426194
|View full text |Cite
|
Sign up to set email alerts
|

A Global Sensitivity Analysis of Soil Parameters Associated With Backscattering Using the Advanced Integral Equation Model

Abstract: A profound and comprehensive understanding of the sensitivity of soil parameters related to backscattering coefficient is significant for the use of active microwave algorithms for soil moisture inversion. This paper presents a global sensitivity analysis (SA) based on the Advanced Integral Equation Model for soil moisture retrieval. The analysis involves diverse parameter ranges, sensor frequencies, incidence angles, surface correlation functions, and polarizations across various experiments. The primary obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 50 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…The EFAST is a well-recognized global SA algorithm that is especially widely applied in the sensitivity analysis for nonlinear models [11], such as the Biome-BGC model [50], crop growth model [12], canopy reflectance model [51], microwave remote sensing models [18]. The algorithm utilizes the main sensitivity index (MSI) and total sensitivity index (TSI) to quantify the sensitivity of the model outputs on various model inputs.…”
Section: Extended Fourier Amplitude Sensitivity Test (Efast)mentioning
confidence: 99%
See 2 more Smart Citations
“…The EFAST is a well-recognized global SA algorithm that is especially widely applied in the sensitivity analysis for nonlinear models [11], such as the Biome-BGC model [50], crop growth model [12], canopy reflectance model [51], microwave remote sensing models [18]. The algorithm utilizes the main sensitivity index (MSI) and total sensitivity index (TSI) to quantify the sensitivity of the model outputs on various model inputs.…”
Section: Extended Fourier Amplitude Sensitivity Test (Efast)mentioning
confidence: 99%
“…By comparing the two cases, it can be seen that the ranges of the parameter significantly influenced their sensitivities and importance order [18]. The range selected in the first experiment was narrower and limiting some important but small parameters, such as α q , so the range was given in the second experiment was suggested for FBEM.…”
Section: Parameters' Si Variation With Parameter Rangementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Vijay estimated soil moisture through the improved WCM [23], and Kumar used Sentinel-1 data to estimate winter wheat crop growth parameters [15]. These studies showed that C-band synthetic aperture radar data have unique advantages in soil moisture estimation, but the backscatter signal is susceptible to the influence of surface vegetation and surface roughness [24]. The interaction between vegetation and radar scattering signals is more complicated, which increases the uncertainty of soil moisture retrieval [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The SAR backscattering coefficient is sensitive to soil dielectric constant, which is directly related to soil moisture content, laying a solid physical foundation for microwave remote sensing retrieval of soil moisture [13]. However, in addition to being controlled by soil dielectric properties, the backscattered signal is strongly influenced by vegetation and surface roughness [14]. The quantification of the respective contributions from vegetation and surface roughness affects the accuracy of soil moisture retrieval.…”
Section: Introductionmentioning
confidence: 99%